A Phenomenological Study on Students' Interest in Vocabulary Acquisition Through Digital Game-Based Learning - Bungsudi, Bungsudi; Priona, Faidzun Jatur; Yunianti, Eka Pratiwi (English Education and Literature Journal (E-Jou), 2025)
Amid the increasing demand for emotionally resonant and learner-driven instruction in EFL contexts, this study offers a novel exploration of how Digital Game-Based Learning (DGBL) can transform vocabulary acquisition into an affective, immersive, and socially collaborative experience. Adopting a phenomenological approach, the research investigates the lived experiences of 13 second-semester EFL students at Universitas Aisyah Pringsewu as they engaged with gamified platforms such as Wordwall. Through Interpretative Phenomenological Analysis, five key themes emerged: heightened learner interest, enhanced peer interaction, improved retention through contextual and repeated exposure, minor but manageable technological barriers, and deep emotional engagement throughout the learning process. The results indicate that DGBL not only supports cognitive aspects of vocabulary learning but also stimulates learners’ motivation, confidence, and autonomous behavior. These findings highlight the pedagogical potential of integrating digital games into EFL classrooms to enrich both the cognitive and emotional dimensions of language learning